Reclaiming space for learning in liturgical contexts: Cracks in the maxim of the uselessness of liturgical ritual - Barnard, Marcel; Wepener, Cas (Hervormde teologiese studies, 2012)
The problem addressed in this article is, that empirical and theoretical research appears to demonstrate that liturgy often aims at certain results. This, however, puts the widely accepted notion in Liturgical Studies of the so-called uselessness of liturgical ritual under pressure. Against this background in Liturgical Studies the aim of this article is to reclaim space in academic discourses on liturgy for learning in liturgical contexts. The latter is done by presenting several liturgical models, revisiting arguments regarding the (non) functionality of ritual or religion and also by reflecting on ritual-liturgical data that the authors personally collected as part of two research projects.